Umbral del dolor en personas normotensas con historia familiar de hipertensión arterial. Pain threshold in people with family history normotensive hypertension - Chonate Urtecho, Luis Eduardo (2015)
In order to analyze whether the pain threshold in normotensive people with a family history of hypertension is high pain thresholds at the level of the second rib and knee bilaterally 36 normotensive patients was measured with and without family history of hypertension. The pain threshold values were 2.3, 3.4, 2.1, 3.2 Kgf in normotensive with no family history of hypertension; and 3.6, 4.1, 2.9 and 3.8 Kgf in normotensive with a family history of hypertension. It was observed that the highest and lowest values were obtained for the same trigger points, as well as the Levene test quality variance and t test for equality of means, the difference was significant. We conclude that normotensive with a family history of hypertension have higher thresholds than those without family history of hypertension pain